Comparative Analysis of Servicescape of Soekarno-Hatta International Airport Terminal 3 and Sanya Phoenix International Airport Terminal 2, Hainan, China on Indonesian Tourist Satisfaction - Desty Ferentya, Marsha; Mbulu, Yustisia Pasfatima; Nasution, Fairly Ivana Luqiana; Amanda, Marcela Dwi; Arzad, Muhammad Fariz; Yayang Permatasari; Yesa Putrilia Inaya; Aisyah Puspita Riani (Politeknik Pariwisata NHI Bandung, 2025)
This study compares the servicescape at Soekarno-Hatta International Airport Terminal 3 andSanya Phoenix International Airport Terminal 2, Hainan, China, and its impact on Indonesian touristsatisfaction. This study uses a descriptive quantitative approach with the SEM analysis methodusing the Smart PLS 3.2.9 program with sampling using the Non-Probability Sampling Technique.Data were collected from 390 respondents who had used services at both airports. The analysisresults at Soekarno-Hatta International Airport Terminal 3 show that environmental conditions andsigns, symbols, and artifacts positively influence tourist satisfaction. In contrast, space, layout, andfunction elements do not show a significant influence. Meanwhile, at Sanya Phoenix InternationalAirport Terminal 2, Hainan, China, it shows that environmental conditions, space, layout, andfunction elements and signs, symbols, and artifacts do not positively influence tourist satisfaction.This study provides insight into the importance of airport design and services in improving thetourist experience. These findings are expected to be a reference for airport managers to improvethe quality of services and facilities offered.